A NOVEL GRAPHICAL PASSWORD CLUSTERING METHOD FOR FAULT TOLERANCE MECHANISM - Mohd Sidek Fadhil Mohd Yunus (Tesis, 2020)
This research was aimed to adapt the digital image clustering (DIC) technique to fix the issue where the faulty PassPix would be recognized having the same group as the original PassPix.